Plasmid-associated transfer of tetracycline resistance in Bacteroides ruminicola. - Flint, H J (1988)
Tetracycline resistance was transferred at frequencies between 10(-7) and 10(-6) per recipient cell in anaerobic matings between two strains of the strictly anaerobic rumen bacterium Bacteroides ruminicola. The donor strain, 223/M2/7, was a multiple-plasmid-bearing tetracycline-resistant strain from the ovine rumen, and the recipient, F101, was a rifampin-resistant mutant of B14, a bovine strain belonging to B. ruminicola subsp. brevis. Resistance transfer could occur in the presence of DNase, but not in dummy mating mixtures in which filtrate from a donor culture replaced donor cells. Acquisition of tetracycline resistance by the recipient was accompanied by the appearance of a 19.5-kilobase pair plasmid (designated pRRI4) which was homologous with a plasmid of similar size and restriction pattern present in the donor strain. A transconjugant (F115) carrying pRRI4 was also able to act as a donor of tetracycline resistance and plasmid DNA in matings with another recipient. Derivatives of F115 that had spontaneously lost tetracycline resistance lacked detectable plasmid DNA. It is concluded that pRRI4 mediated the transfer of tetracycline resistance. Transfer of resistance was not detectably enhanced by pregrowth of the donor in medium containing tetracycline. Transfer of tetracycline resistance was not detected from 223/M2/7 to a strain, 23 belonging to B. ruminicola subsp. ruminicola.